Transformational leadership and horizontal trust as antecedents of team performance in the healthcare context. - Olvera-Calderón, Juana; LLorens-Gumbau, Susana; Acosta-Antognoni, Hedy; Salanova-Soria, Marisa (Anales de Psicología / Annals of Psychology, 2017)
The present study analyzes the mediator role of work-team trust (i.e., horizontal trust) in the relationship between transformational leadership, as a social resource, and team performance (i.e., intra- and extra-role performance), as suggested by the HERO model (HEalthy & Resilient Organizations Model; Salanova, Llorens, Cifre, & Martínez, 2012). The sample corresponds to 388 workers nested in 54 work teams from four organizations in the healthcare sector. Horizontal trust and transformational leadership were assessed by the work teams, and performance was assessed by the supervisors of these teams. Structural Equations models reveal, as expected, that horizontal trust has a fully mediating role between transformational leadership perceived at the team level and team performance assessed by the supervisor.